Claude Bernard: bicentenary of birth and his main contributions to neurology - Marleide da Mota Gomes; Eliasz Engelhardt (Arquivos de Neuro-Psiquiatria)
Claude Bernard (1813-1878) followed two main research paths: the chemical and physiological study of digestion and liver function, along with experimental section of nerves and studies on sympathetic nerves. Curare studies were, for example, of longstanding interest. His profound mental creativity and hand skillfulness, besides methodology quality, directed his experiments and findings, mainly at the Collège de France. His broader and epistemological concerns were carried out at the Sorbonne and later at the Muséum national d'Histoire naturelle. His insight gave clues to define the “ milieu intérieur”, later known as “homeostasis”, and grasp the brain complexity. Bernard followed and surpassed his master François Magendie who also fought against dogmas and laid the foundations of experimental medicine, and its main heinous tool – vivisection. Bernard created the methodological bases of experimental medicine, and collected honors as a renowned researcher.